El arte y su impacto critico a partir de la tecnología - Campoverde Azuero, Jefferson Stiven (2017)
The connection between art and new technologies at present has allowed a didactic performance, where artists take advantage of this tool as a method or construction of their artistic proposals. Probably plays the creativity, the need and the purpose that the work plays for the manipulation and execution of the new technologies in the artistic field. From the twentieth century, art undergoes an extreme change where it is completely removed from the figurative and conventional, where the work of art is externalized in multiple forms of elaboration and grant a degree of complexity to the viewer, so the object Artistic changes from its traditional to take a more sublime role as is the theoretical-conceptual discourse. This is where art includes technology as a tool that is capable of facilitating the understanding and objectivity of the creator. As expressed by Marcel Duchamp in his sculptural works called ready made ready and made, taking daily objects or elements without changing their general form, the artist provides a theoretical-conceptual foundation allowing the habitual object to become an object with artistic value generating Discourse and criticism. Taking these measures that have taken place throughout history and with the help of technology seeks to rescue the low cultural value in our society, since at the same time technology has generated an addiction or cybernetic culture due to the misuse of social networks.